Transformational Leadership as A Catalyst For Good Governance and Sustainable Development in Nigeria - Rasheed, Isau (Journal of Techno-Social, 2026)
Transformational leadership has increasingly been recognized as a crucial mechanism for promoting effective governance and sustainable development, particularly in developing democracies such as Nigeria. This paper examined the significance of transformational leadership in strengthening good governance and sustainable development in Nigeria. The study specifically addressed the persistent challenges of institutional inefficiency, policy inconsistency, and weak adherence to ethical principles of equity, transparency, and accountability among successive political administrations. Although existing literature acknowledges the relevance of transformational leadership, insufficient attention has been given to its integrative capacity in addressing governance deficits and developmental challenges in Nigeria. The study adopted transformational leadership theory as its analytical framework in order to identify an appropriate leadership approach capable of fostering good governance and sustainable national development. Data for the study were collected from secondary sources, including scholarly publications, official reports, and relevant documented materials. Findings revealed that successive political leadership in Nigeria has been characterized by policy inconsistencies and inadequate developmental commitment, largely resulting from the absence of motivational inspiration and visionary leadership capable of stimulating collective national transformation. The study further found that transformational leadership possesses the capacity to promote inclusiveness, enhance institutional effectiveness, encourage productivity, and strengthen mechanisms for sustainable development. The paper concluded that redefining political leadership through transformational leadership principles is essential for achieving radical transformation, good governance, and sustainable national progress in Nigeria. Consequently, the study recommends the adoption of transformational leadership approaches that emphasize inclusivity, accountability, individual consideration, and enduring solutions to developmental challenges across the country.